Darolutamide and health-related quality of life in patients with non-metastatic castration-resistant prostate cancer: An analysis of the phase III ARAMIS trial. (September 2021) - Smith, Matthew R.; Shore, Neal; Tammela, Teuvo L.; Ulys, Albertas; Vjaters, Egils; Polyakov, Sergey; Jievaltas, Mindaugas; Luz, Murilo; Alekseev, Boris; Kuss, Iris; Le Berre, Marie-Aude; Mohamed, Ateesha F.; et al.
Abstract: Background: In the ARAMIS trial, darolutamide plus androgen deprivation therapy (ADT) versus placebo plus ADT significantly improved metastasis-free survival (MFS), overall survival (OS) and time to pain progression in patients with non-metastatic castration-resistant prostate cancer (nmCRPC). Herein, we present analyses of patient-reported health-related quality of life (HRQoL) outcomes. Patients and methods: This double-blind, placebo-controlled, phase III trial randomised patients with nmCRPC and prostate-specific antigen doubling time ≤10 months to darolutamide 600 mg ( n  = 955) twice daily or matched placebo ( n  = 554) while continuing ADT. The primary end-point was MFS; the secondary end-points included OS and time to pain progression. In this analysis, HRQoL was assessed by the time to deterioration using the Functional Assessment of Cancer Therapy–Prostate (FACT-P) prostate cancer subscale (PCS) and the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Prostate Cancer Module (EORTC QLQ-PR25) subscales. Results: Darolutamide significantly prolonged time to deterioration of FACT-P PCS versus placebo (hazard ratio [HR] 0.80, 95% confidence interval [CI] 0.70–0.91; P =  0.0005) at the primary analysis (cut-off date: 3rd September 2018). Time to deterioration of EORTC QLQ-PR25 outcomes showed statistically significant delays with darolutamide versus placebo for urinary (HR 0.64, 95% CI 0.54–0.76; P  < 0.0001) and bowel (HR 0.78, 95% CI 0.66–0.92; P =  0.0027) symptoms. Time to worsening of hormonal treatment–related symptoms was similar between the two groups. Conclusion: In patients with nmCRPC who are generally asymptomatic, darolutamide maintained HRQoL by significantly delaying time to deterioration of prostate cancer–specific quality of life and disease-related symptoms versus placebo. Highlights: Men with asymptomatic non-metastatic castration-resistant prostate cancer benefit from treatments that maintain quality of life (QoL). Darolutamide significantly delays deterioration of urinary and bowel symptoms. Change in hormone treatment–related symptoms was similar for darolutamide and placebo. Darolutamide increases metastasis-free survival and overall survival while maintaining prostate cancer–specific QoL.